2003
DOI: 10.37855/jah.2003.v05i02.17
|View full text |Cite
|
Sign up to set email alerts
|

The impact of panicle and shoot pruning on inflorescence and yield related developments in some mango cultivars.

Abstract: The effect of different kinds of pruning treatments was studied on Keitt and Tommy Atkins cultivars over two seasons. The trial was conducted at Bavaria Estate, around Hoedspruit area, Northern province of South Africa (latitude: 24o25'S; longitude: 30 54'E; elevation: 600m). With regard to inflorescence development, panicle pruning (during full bloom) at the point of apical bud attachment proved to induce re-flower, more rapid fruit development and more fruit per panicle than the other panicle pruning treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…It has also been clearly demonstrated that leaf/fruit ratio and water stress have an impact on the import of carbon assimilates in mango 5. Depending on the variety, tree management, including the pruning of specific shoots or the selection of inflorescences, can have an impact on firmness, sugar content and acidity in mango fruit 6…”
Section: Introductionmentioning
confidence: 99%
“…It has also been clearly demonstrated that leaf/fruit ratio and water stress have an impact on the import of carbon assimilates in mango 5. Depending on the variety, tree management, including the pruning of specific shoots or the selection of inflorescences, can have an impact on firmness, sugar content and acidity in mango fruit 6…”
Section: Introductionmentioning
confidence: 99%
“…But the productivity is very poor (7.3 MT/ha) when compared other mango producing countries due to use of poor planting material, traditional method of planting system, lack of awareness in training and pruning system, cultivation of alternate bearing varieties and poor orchard management (Balamohan and Gopu, 2014). Yeshitela et al, (2003) reveals that pruning at the point of apical bud attachment induced reflowering, more rapid fruit development and more fruits per panicle. Treatments such as pruning that manipulate timing of flush development and synchronize canopy flushing have been successful in increasing flowering intensity (Yeshitela et al, 2005).…”
Section: Canopy Managementmentioning
confidence: 99%
“…This may be due to scarcity of photosynthates or higher utilization of soluble assimilates in regular season. Oosthuyse and Jacobs [13] and Yeshitela [14] found marginally higher fruit weight in hand de-blossomed treatments over untreated trees (control). [15] and Kaviarasu et al [16].…”
Section: Off Season Fruitingmentioning
confidence: 99%